Review of The Picture Postcard: A New Window into Edwardian Ireland, by Ann Wilson - Lauren Alex O'Hagan (Review of Irish Studies in Europe)
Review of The Picture Postcard: A New Window into Edwardian Ireland , by Ann Wilson (Oxford: Peter Lang, 2021). 256 pp. ISBN 978-1-78874-079-1 HC, €49.40.